2012
DOI: 10.1159/000341659
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Laparoscopic Staging to Avoid Adjuvant Chemoradiation following Radical Surgery in Patients with Early Cervical Cancer

Abstract: Purpose: To determine the rate of unavoidable adjuvant chemoradiation (RCTX) due to histologic results after radical surgery in patients with early cervical cancer. Patients and Methods: Between May 2004 and July 2011, 448 consecutive patients diagnosed with invasive cervical cancer stage IA1 L1 to IIA underwent laparoscopic staging at the Department of Gynecology and Gynecologic Oncology at Charité Berlin. Only in patients without lymph node metastases (n = 394) on frozen section, radical operation was contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…This high rate is comparable with other reports. 6,20 The main goals in the treatment of early cervical cancer are to achieve the high cure rate with an overall 5-year survival in the range of 90%, to minimize possible short and long-term morbidities and to preserve fertility and ovarian function when it is relevant. Although in early-stage disease, the survival outcome is similar after either primary surgery or primary RT, 5,6,25-27 surgery is more commonly utilized than RT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This high rate is comparable with other reports. 6,20 The main goals in the treatment of early cervical cancer are to achieve the high cure rate with an overall 5-year survival in the range of 90%, to minimize possible short and long-term morbidities and to preserve fertility and ovarian function when it is relevant. Although in early-stage disease, the survival outcome is similar after either primary surgery or primary RT, 5,6,25-27 surgery is more commonly utilized than RT.…”
Section: Discussionmentioning
confidence: 99%
“…This undesirable 2-modality treatment was also reported by others who reported the rate of adjuvant radiation between 10% and 64%, depending on the years of the study and the criteria chosen for radiation. 6,13,[16][17][18][19][20] Historically, adjuvant pelvic RT was indicated in cases of lymph nodes metastasis, positive surgical margins, or PI. In these cases, which are considered high risk because of these prognostic factors, recurrences are more frequent and when one or more of these factors are found, the 5-year survival can drop to 40% to 70%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that laparoscopic staging is a feasible and safe procedure. Marnitz et al [ 5 ] published in 2012 the results of a prospective study. They demonstrated that in patients with early cervical cancer, laparoscopic staging with the use of frozen section of the lymph nodes successfully tailored the treatment.…”
Section: Staging and Re-stagingmentioning
confidence: 99%